Body surface mapping of P-waves in sinus rhythm to predict recurrence following cardioversion for atrial fibrillation - Antoun, Ibrahim; Li, Xin; Kotb, Ahmed; Barker, Joseph; Mavilakandy, Akash; Koev, Ivelin; Vali, Zakariyya; Somani, Riyaz; Ng, G. André (Frontiers in Cardiovascular Medicine, 2024)
Background Direct current cardioversion (DCCV) is used as elective and emergency rhythm control for atrial fibrillation (AF). We aimed to explore the role of P-wave parameters measured during sinus rhythm using body surface mapping (BSM) in predicting successful DCCV for persistent atrial fibrillation (persAF) at 12 months. Methods This case–control study included 56 males >18 years old who underwent DCCV for persAF. P-wave parameter collection after DCCV for AF was done using 128 unipolar leads. A band-pass filter of 1–50 Hz was utilised. Corrected P-wave duration (PWDc), P-wave amplitude, and P-wave dispersion were measured to predict 12-month outcomes and time of recurrence. Results The mean age was 64 ± 4 years, and 23 patients (44%) were on amiodarone. The 12-month success rate was 44% (n = 23), while the rest reverted to AF after 2.6 ± 0.4 months. The parameters were comparable between successful and failed DCCV in the entire cohort and patients not on amiodarone. In patients on amiodarone, patients with failed arms had higher PWDc than those with successful arms (188 vs. 150 ms, P = 0.04). Receiver operator characteristic curve analysis for PWDc in the amiodarone cohort showed an area under the curve (AUC) of 0.75 and P = 0.049. A recurrence cut-off >161 ms had a sensitivity of 69% and a specificity of 100%, with a hazard ratio of 10.7, P = 0.004. The parameters were not predictive of the time of recurrence. Conclusion In patients on amiodarone, increased PWDc measured using BSM was associated with higher AF recurrence at 12 months following DCCV for persAF.